INTEGRAL EVALUATION OF NEUTRAL ENDOPEPTIDASE INHIBITORS AS POSSIBLE ANTIHYPERTENSIVE AGENTS BY MEANS MOLECULAR MECHANICS, FREE ENERGY CALCULATION AND ADME-TOX PROPERTIES. - Castillo-Garit, Juan Alberto; Lamazarez Arcia, Emilio; Cañizarez Carmenate, Yudith; Mena-Ulecia, Karel (Journal of the Chilean Chemical Society, 2023)
The most important mechanisms in the blood pressure regulation, fluid volume and sodium-potassium balance in humans is the renin-angiotensin-aldosterone system (RAAS). This regulatory pathway plays a critical role in modulating cardiac function and vascular tone. An alteration in any of the molecules that make up this system (RAAS) could contribute to the development of arterial hypertension. In this important mechanisms, the neutral endopeptidase, also called Neprilysin (NEP) is the main enzyme for the degradation of natriuretic, therefore, it is essential proteins in controlling blood pressure. In this work, we have used docking methodology, molecular dynamics simulationa and free energy calculations method (MM-PBSA), to comprehensively evaluate the inhibitory behavior of some ligands obteined from consulted literature. The principal results obtained shown these ligands were adequately oriented in the NEP pocket. The Lig783, Lig2177, and Lig3444 compounds were those with better dynamic behavior. The energetic components that contribute to the complex’s stability are the electrostatic and Van der Waals components; however, when the ADME-Tox properties were analyzed, we conclude that the best possible anti-hypertensive candidate are Lig783 and Lig3444.